IT-based product innovation strategies for small firms. Issue 6 (23rd July 2020) - Ko, Wai Wai (Joyce); Chen, Cheng-Hao Steve; Liu, Gordon; Nguyen, Bang; Takeda, Sachiko
Abstract : Purpose: This study connects the theoretical concepts of strategic orientation and information technology (IT)-based product innovation strategy to suggest that several key factors can help small firms to develop IT-based product innovation strategies. Design/methodology/approach: With data from 245 useable questionnaires (response rate 25.18%) from UK-based small firms in the high-tech industry, the research model was tested and validated. Findings: Findings show that information technology support for core competencies mediates the relationship between strategic orientation and IT-enabled product innovation (ITEPI). Specifically, by distinguishing the different types of strategic orientation and information technology support for core competencies, the study finds that IT support for market access competency (ITMA) mediates the market orientation–ITEPI relationship, while IT support for functionality-related competency (ITFR) mediates the technology orientation–ITEPI relationship. Academic implications arising from the findings are discussed and managerial propositions provided. Originality/value: This study offers a fresh theoretical angle from which to understand the factors that contribute to ITEPI. More specifically, we argue that strategic orientation reflects managers' focus to pursue certain activities, and that ITEPI serves as organizational activity. Further, this study also extends relevant research in the field of strategy, IT and innovation. It provides a more nuanced picture of how strategic orientation affects ITEPI.